War traditions from the Qumran caves: re-thinking textual stability and fluidity in the war text manuscripts - Vanonen, Hanna (Studies on the texts of the desert of Judah, 2022)
In this volume, Hanna Vanonen offers a fresh view to the Milhamah and Sefer ha-Milhamah manuscripts by producing a thorough close-reading analysis of them, paying attention not only to their contents but also to manuscripts as material artifacts. Vanonen demonstrates that studying the stability and instability of the War traditions does more justice to the complex material than a traditional chronological literary-critical model. In addition, Vanonen argues that at least liturgical use and study purposes may have created needs for producing different manuscripts that were simultaneously important